Trajectories of Low Back Pain From Adolescence to Young Adulthood - Coenen, P.; Smith, Anne; Paananen, M.; O'Sullivan, Peter; Beales, Darren; Straker, Leon (John Wiley & Sons, Inc., 2017)
Objective: Despite the high prevalence and burden of low back pain (LBP), understanding of its course during the transition from adolescence to adulthood is limited. The aim of this study was to identify and describe trajectories of LBP and its impact among a general population sample followed from adolescence to young adulthood. Methods: Data from followup assessments at years 17, 20, and 22 of the Western Australian Pregnancy Cohort (Raine) Study were used (n = 1,249). Self-reported LBP and its impact on daily life were assessed, and latent class analysis was used to identify clusters. Resultant clusters were profiled on sex, waist circumference, diagnosed comorbid pain, and health-related quality of life. Results: Four clusters were identified: a cluster of participants with a consistently low prevalence of LBP and its impact (53%) during the period from adolescence to young adulthood, a cluster with an increase in the prevalence of LBP and its impact (22%), a cluster with a decrease in the prevalence of LBP and its impact (15%), and a cluster with a consistently high prevalence of LBP and its impact (10%). These clusters differed markedly on the profiling variables. Conclusion: The identified clusters provide unique information on LBP and its impact during the transition from adolescence to young adulthood. Consideration of these trajectories could be important in the design of early prevention and management strategies.